Pendampingan Peningkatan Keterampilan dan Kemampuan Ekonomi Mandiri Para Hamba Tuhan GBI di Ladang Misi dalam Masa Pandemi Covid-19 - Fransiskus Irwan Widjaja; Rubin Adi Abraham; Daniel Ginting; Antonius Natan; Ardy Lahagu; Rini Rini; Ronald Sianipar; Benteng Martua Mahuraja Purba; Ferdinandes Petrus Bunthu (Real Coster : Jurnal Pengabdian kepada Masyarakat, 2022)
This activity started from data from the Bethel research center, the GBI Synod which conducted research in May-June 2020 throughout Indonesia. Surprisingly 64% of the total GBI officials are experiencing economic hardship. Based on this need, the Department of Mission and Tribal Church Planting was neglected by the GBI synod, in collaboration with the Community Service Team (PkM) of STT Real Batam, which took the initiative to hold a national webinar. The purpose of this assistance is to improve the skills of God's servants in procuring daily needs and increase the knowledge of pioneering servants of God or pastors in the mission field for economic strengthening in the context of independent mission services. The method used is debriefing by practitioners in their respective fields, workshops, questions and answers, discussions. Even though this activity is carried out zooming in on the pandemic, this activity has a very positive impact on God's servants in growing an interest in being independent from finance. In carrying out this community service activity for God's servants, pioneers, and spearheads of service, it is carried out through sustainable missionomic webinars.Keywords: economy; servant of God; Skills; accompaniment; sustainable missionomic AbstrakKegiatan ini bermula dari data pusat penelitian Bethel, Sinode GBI yang melakukan penelitian pada bulan Mei-Juni 2020 di seluruh Indonesia. Sangat mengejutkan 64% dari total pejabat GBI mengalami kesulitan ekonomi. Berdasarkan kebutuhan itu, maka Departmen Misi dan Penanaman Gereja Suku terabaikan sinode GBI bekerjasama dengan Tim Pengabdian kepada Masyarakat (PkM) STT Real Batam berinisiatif mengadakan webinar nasional. Tujuan dari pendampingan ini adalah untuk meningkatkan ketrampilan hamba Tuhan dalam pengadaan kebutuhan hari-hari dan menambah pengetahuan para hamba Tuhan perintis atau gembala di ladang misi untuk penguatan ekonomi dalam rangka pelayanan misi mandiri. Metode yang digunakan adalah pembekalan oleh praktisi di bidang masing-masing, workshop, tanya jawab, diskusi. Sekalipun aktifitas ini dilakukan secara zooming pada pandemi, namun kegiatan ini sangat berdampak positif kepada hamba Tuhan dalam menumbuhkan minat mandiri dari keuangan. Dalam melakukan kegiatan pengabdian masyarakat ini terhadap hamba Tuhan, perintis, dan ujung tombak pelayanan, dilaksanakan melalui webinar suistainable missionomic.Kata kunci: ekonomi; hamba Tuhan; keterampilan; pendampingan; sustainable missionomic